The beta-adrenergic agonist salbutamol modulates neuromuscular junction formation in zebrafish models of human myasthenic syndromes. (16th February 2018) - McMacken, Grace; Cox, Dan; Roos, Andreas; Müller, Juliane; Whittaker, Roger; Lochmüller, Hanns
Abstract: Inherited defects of the neuromuscular junction (NMJ) comprise an increasingly diverse range of disorders, termed congenital myasthenic syndromes (CMS). Therapies acting on the sympathetic nervous system, including the selective β2 adrenergic agonist salbutamol and the α and β adrenergic agonist ephedrine, have become standard treatment for several types of CMS. However, the mechanism of the therapeutic effect of sympathomimetics in these disorders is not understood. Here, we examined the effect of salbutamol on NMJ development using zebrafish with deficiency of the key postsynaptic proteins Dok-7 and MuSK. Treatment with salbutamol reduced motility defects in zebrafish embryos and larvae. In addition, salbutamol lead to morphological improvement of postsynaptic acetycholine receptor (AChR) clustering and size of synaptic contacts in Dok-7-deficient zebrafish. In MuSK-deficient zebrafish, salbutamol treatment reduced motor axon pathfinding defects and partially restored the formation of aneural prepatterned AChRs. In addition, the effects of salbutamol treatment were prevented by pre-treatment with a selective β2 antagonist. Treatment with the cyclic adenosine monophosphate (cAMP) activator forskolin, replicated the effects of salbutamol treatment. These results suggest that sympathomimetics exert a direct effect on neuromuscular synaptogenesis and do so via β2 adrenoceptors and via a cAMP-dependent pathway.